Respuesta :
For this case, the first thing we must do is define a variable.
We have then:
x: unknown number.
First number: 2x - 4
Second number: x
The product of the numbers is:
[tex] y = x (2x-4) [/tex]
Rewriting:
[tex] y = 2x ^ 2-4x [/tex]
Deriving the equation we have:
[tex] y '= 4x-4 [/tex]
We equal zero and clear x:
[tex] 4x - 4 = 0 x = 4/4 x = 1[/tex]
Then, the first number is:
[tex] 2x - 4 = 2 (1) - 4 = 2 - 4 = - 2 [/tex]
Answer:
First number: -2
Second number: 1
We have then:
x: unknown number.
First number: 2x - 4
Second number: x
The product of the numbers is:
[tex] y = x (2x-4) [/tex]
Rewriting:
[tex] y = 2x ^ 2-4x [/tex]
Deriving the equation we have:
[tex] y '= 4x-4 [/tex]
We equal zero and clear x:
[tex] 4x - 4 = 0 x = 4/4 x = 1[/tex]
Then, the first number is:
[tex] 2x - 4 = 2 (1) - 4 = 2 - 4 = - 2 [/tex]
Answer:
First number: -2
Second number: 1
Answer:
Numbers are -2 and 1.
Step-by-step explanation:
Let x be the second number,
⇒ First number = 4 less than twice a second number
= 2 × Second number - 4
= 2x - 4
Thus, the product of first and second number is,
[tex]f(x) = x(2x-4)[/tex]
[tex]\implies f(x) = 2x^2 - 4x[/tex]
Differentiating with respect to x,
[tex]f'(x) = 4x -4[/tex]
Again differentiating with respect to x,
[tex]f''(x) = 4[/tex]
Now, for maximum or minimum,
[tex]f'(x)=0[/tex]
[tex]\implies 4x - 4 = 0\implies 4x = 4\implies x = 1[/tex]
Since, for x = 1, f''(x) = Positive,
Therefore, the function f(x) is minimum for x = 1,
⇒ The product is smallest for x = 1,
Hence, the second number = x = 1,
And, first number = 2x - 4 = 2 - 4 = -2